Secukinumab (AIN-457) for the treatment of Psoriasis. Issue 2 (1st February 2016) - Jaleel, Tarannum; Elmets, Craig; Weinkle, Allison; Kassira, Sama; Elewski, Boni
Summary: Secukinumab (also known as AIN-457) is a human monoclonal antibody targeting IL-17A, which has been recently FDA-approved for the treatment of moderate to severe psoriasis and psoriatic arthritis with coexistent moderate to severe plaque psoriasis based on clinical trials demonstrating excellent efficacy. This review will address the rationale for targeting the IL-23/Th17/IL-17 axis, the role of IL-17 and Th17 cells in psoriasis and other chronic inflammatory diseases, and will examine pre-clinical studies, pharmacologic properties, clinical efficacy, and the safety profile of secukinumab.